Climatic, weather, and socio-economic conditions corresponding to the mid-17th-century eruption cluster - Stoffel, Markus; Corona, Christophe; Ludlow, Francis; Sigl, Michael; Huhtamaa, Heli; Garnier, Emmanuel; Helama, Samuli; Guillet, Sébastien; Crampsie, Arlene; Kleemann, Katrin; Camenisch, Chantal; McConnell, Joseph; et al. (Climate of the Past, 2022)
The mid-17th century is characterized by a cluster of explosive volcanic eruptions in the 1630s and 1640s, climatic conditions culminating in the Maunder Minimum, and political instability and famine in regions of western and northern Europe as well as China and Japan. This contribution investigates the sources of the eruptions of the 1630s and 1640s and their possible impact on contemporary climate using ice core, tree-ring, and historical evidence but will also look into the socio-political context in which they occurred and the human responses they may have triggered. Three distinct sulfur peaks are found in the Greenland ice core record in 1637, 1641–1642, and 1646. In Antarctica, only one unambiguous sulfate spike is recorded, peaking in 1642. The resulting bipolar sulfur peak in 1641–1642 can likely be ascribed to the eruption of Mount Parker (6∘ N, Philippines) on 26 December 1640, but sulfate emitted from Komaga-take (42∘ N, Japan) volcano on 31 July 1641 has potentially also contributed to the sulfate concentrations observed in Greenland at this time. The smaller peaks in 1637 and 1646 can be potentially attributed to the eruptions of Hekla (63∘ N, Iceland) and Shiveluch (56∘ N, Russia), respectively. To date, however, none of the candidate volcanoes for the mid-17th century sulfate peaks have been confirmed with tephra preserved in ice cores. Tree-ring and written sources point to cold conditions in the late 1630s and early 1640s in various parts of Europe and to poor harvests. Yet the early 17th century was also characterized by widespread warfare across Europe – and in particular the Thirty Years' War (1618–1648) – rendering any attribution of socio-economic crisis to volcanism challenging. In China and Japan, historical sources point to extreme droughts and famines starting in 1638 (China) and 1640 (Japan), thereby preceding the eruptions of Komaga-take (31 July 1640) and Mount Parker (4 January 1641). The case of the eruption cluster between 1637 and 1646 and the climatic and societal conditions ...